Perceived Family Function and Associated Predictors in Nurses: A Cross-Sectional Study - Zeng, Wen; Fang, Qian; Wang, Cui; Tong, Beibei; Li, Dan; Zou, Ziqiu; Liu, Peiyuan; Yao, Yuanrong; Shang, Shaomei (Frontiers in Psychiatry, 2022)
Background: Evidence of family function in clinical nurses remains limited even though nurses play a core role in the health care system. Objectives: The current study was to evaluate the family function of the Chinese clinical nurses, and to explore associated predicting factors. Methods: A multi-center cross-sectional anonymous online survey was carried out. Chinese Family Function Scale was used in the study. Spearman’s rank correlation analysis, Mann-Whitney U test, or Kruskal-Wallis H test was performed in the univariate analysis. The pairwise comparison method was used to determine whether the difference was significant between pair groups. Categorical regression (optimal scaling regression) was the main method to analyze factors that had been confirmed to be statistically significant in the univariate analysis. Results: 19422 nurses completed the online questionnaires. The median of the nurse’s perceived family function score was 3 (Inter-quartile Range: IQR 2-5). The univariate analysis suggested age (P=0.004), the highest education level (P<0.001), the hospital level (P<0.001), working years (P=0.031), rotation shift status (P<0.001), working department (P<0.001), marital status (P<0.001), the number of children (P<0.001), and monthly income per family member (P<0.001) were related to the nurses’ perceived family function. However, the multivariate analysis showed that highest education level (P<0.001), the hospital level (P<0.001), rotation shift status (P<0.001), working department (P<0.001), number of children (P<0.001), monthly income per family member (P<0.001) were significantly associated with family function. Moreover, the importance of the factors was the number of children (49.1%), monthly income per family member (20.7%), rotation shift status (12.4%), the highest education level (8.0%), the hospital level (7.6%), and working department (2.4%) in turn. Conclusions: The family function was associated with multiple factors, which hints that managers, leaders, and government could make strategies to improve nurses’ family function in order to lead nurses to make balance family and work.